TRANSFORMASI DIGITAL: DAMPAK DAN TANTANGAN TEKNOLOGI INFORMASI DI ERA MODERN - Mangkuanom, Hasanal Hakim; Muslim; Tri Aulya Nisa Br Tarigan; Andika Pratama; Muhammad Aulia (Lembaga Riset dan Inovasi Kreyat Center, 2024)
Digital transformation has transformed business, society, and technology globally. In this journal, we discuss the impact of information technology in the modern era. Information technology is becoming an important role in other transformations; such as accelerating innovation, facilitating global connectivity, and transforming the way we work. While the potential of IT in supporting growth in progress is enormous, such as significant issues that need to be addressed, such as data security, privacy, and digital divide issues. In this article, we provide an overview of the role, impact, and challenges of Information Technology in today's digital age. Through data analysis and case studies, we look at how IT has transformed various sectors, including business, education, healthcare, and government. In addition, we also highlight integrating IT effectively, as well as provide recommendations to overcome these challenges. By comprehensively understanding the role and potential of IT, it is hoped that we can take appropriate steps to utilize this technology optimally and achieve goals that improve the quality of life of society as a whole.